2020
DOI: 10.3390/ijms21176338
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of the Novel Bacteriophage AXL3 against Stenotrophomonas maltophilia

Abstract: The rapid increase in the number of worldwide human infections caused by the extremely antibiotic resistant bacterial pathogen Stenotrophomonas maltophilia is cause for concern. An alternative treatment solution in the post-antibiotic era is phage therapy, the use of bacteriophages to selectively kill bacterial pathogens. In this study, the novel bacteriophage AXL3 (vB_SmaS-AXL_3) was isolated from soil and characterized. Host range analysis using a panel of 29 clinical S. maltophilia isolates shows successful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 67 publications
2
23
0
Order By: Relevance
“…Bacterial phage therapy is gaining traction as a novel approach to refractory cases of extremely multidrug resistant (XDR) bacterial infections; advantages include specificity to the target, limited side effects on the host biome, and lack of major end organ damage [82]. In 2004, Chang et al reported a series of Stenotrophomonas bacteriophages, φSMA1-φSMA8, with an in-depth characterization and discussion of one phage, φSMA5 [83].…”
Section: Phage and Peptide Therapymentioning
confidence: 99%
“…Bacterial phage therapy is gaining traction as a novel approach to refractory cases of extremely multidrug resistant (XDR) bacterial infections; advantages include specificity to the target, limited side effects on the host biome, and lack of major end organ damage [82]. In 2004, Chang et al reported a series of Stenotrophomonas bacteriophages, φSMA1-φSMA8, with an in-depth characterization and discussion of one phage, φSMA5 [83].…”
Section: Phage and Peptide Therapymentioning
confidence: 99%
“…Previous studies have shown that this protein is essential to DNA ejection and phage morphogenesis [44]. However, no comprehensive description exists of the protein's exact activities [45].…”
Section: Specific Features Of the Phage Genomementioning
confidence: 99%
“…Strain FDAARGOS_1044 (accession: NZ_CP065965.1) was predicted to have the most prophage regions with 11, three of which were classified as intact, six as incomplete, and two as questionable, whereas only one strain, AA1 (accession: NZ_CP018756.1), had zero predicted prophage regions. Although many bacteria have phage defense systems to protect against phage predation and possibly prophage integration, these systems, including CRISPR-Cas immunity, have not yet been characterized in S. maltophilia [111][112][113], potentially contributing to the high prevalence of prophage DNA in their genomes.…”
Section: Bacteriophagesmentioning
confidence: 99%
“…intact, six as incomplete, and two as questionable, whereas only one strain, AA1 (accession: NZ_CP018756.1), had zero predicted prophage regions. Although many bacteria have phage defense systems to protect against phage predation and possibly prophage integration, these systems, including CRISPR-Cas immunity, have not yet been characterized in S. maltophilia [111][112][113], potentially contributing to the high prevalence of prophage DNA in their genomes. The high prevalence of prophages in bacterial genomes suggests that phages have played an important role in bacterial evolution [108,114].…”
Section: Bacteriophagesmentioning
confidence: 99%
See 1 more Smart Citation